In situ interfacial engineering enabled mechanically adaptive and highly stretchable liquid metal conductor. (1st February 2022) - Xie, Shuang-Man; Zhao, Xing; Peng, Li-Mei; Yu, Peng; Zha, Xiang-Jun; Ke, Kai; Bao, Rui-Ying; Yang, Ming-Bo; Yang, Wei
Abstract: Liquid metal (LM) based stretchable conductors have broad application due to their excellent conductivity and deformability. However, the poor interfacial interaction between LM and majority of elastic substrates because of the high surface tension of LM, limits the spread of LM on the substrate and the reconciliatory deformation of LM with underlying substrate. Herein, through the specific affinity between the immediately formed oxide layer on surface of eutectic gallium-indium (EGaIn) and carboxyl groups, an in-situ interfacial engineering for LM conductive coating on hydrogen-bonded poly(ethylene oxide)/poly(acrylic acid) (PEO/PAA) elastomers is presented. Particularly, EGaIn patterned on PEO/PAA elastomers can autonomously adapt to the mechanical deformation of substrates to form a stable interface conductive layer, and the slope of deformation ratio between EGaIn layer and PEO/PAA elastomers keeps nearly 1 even at strain of 800%. The design of interfacial interaction also ensures the simultaneous achievement of excellent stretchability and stable conductivity of LM based stretchable electronics, that is, the resistance of the EGaIn conductor will not change significantly and remain below 1 Ω even at a strain of 800%. This work provides guideline for the design of stretchable LM-based conductor. Graphical abstract: Image 1 Highlights: An in-situ interfacial engineering for LM on hydrogen-bonded PEO/PAA elastomers is presented. Strong interaction occurs between oxide layer on surface of EGaIn and carboxyl groups. The slope of deformation ratio between LM layer and PEO/PAA elastomers keeps nearly 1 even at strain of 800%. The resistance of the LM-based conductor can remain below 1 Ω even at a strain of 800%.